Fate of hexaconazole and isoprothiolane in rice, soil and water under field conditions. Issue 1 (2nd January 2016) - Zhang, Kankan; Tang, Mingming; Zhang, Jing; Li, Yanjiao; Han, Xinwei; Pan, Sizhu; Kong, Xinxin; Li, Meichuan; Chen, Hongyu; Zhang, Wen; Zhu, Huijun; Zeng, Song; et al.
ABSTRACT: Residue dissipation of hexaconazole and isoprothiolane in the rice field ecosystem was determined by gas chromatography coupled with electron capture detector. Hexaconazole and isoprothiolane (33% microemulsion) were applied at two dosages, 396 g a.i. ha –1 (the recommended dosage) and 594 g a.i. ha –1 (1.5 times the recommended dosage) in the experimental fields in Guizhou, Hunan and Heilongjiang provinces, China, during 2011–2012. The limits of detection and limits of quantification in brown rice were 0.006 and 0.02 mg kg –1 for hexaconazole, 0.0072 and 0.024 mg kg –1 for isoprothiolane, respectively, and they were much below the maximum residue limits (MRLs, 0.1 mg kg –1 for hexaconazole and 1.0 mg kg –1 for isoprothiolane) set by China. Average recoveries of hexaconazole in water, soil, rice plants and brown rice ranged from 77.3% to 93.8% and for isoprothiolane ranged from 78.1% to 99.9% with relative standard deviations < 10%. The results showed that during harvest, the terminal residue levels of hexaconazole and isoprothiolane in brown rice samples were well below the MRLs of China following the interval of 7 days after last application. Therefore, a dosage of 396 g a.i. ha –1 was recommended, which could be considered as safe to human beings.